Mechanism of the effect of chitosan combined with EICP on the erosion resistance of slopes in open-pit mine dump - Zhile WANG; Yu TIAN; Wei ZHOU; Yi WANG; Rui LI; Yihan GUO; Ya TIAN; Ao LU (Meitan xuebao, 2024)
Most of the open-pit coal mines in China are located in the ecologically vulnerable regions in the north with obvious seasonal rainfall and poor soil layer, where the ecological background is fragile and soil erosion is serious. To improve the outstanding problems of soil erosion and soil and water loss caused by large-scale development of open-pit mines in the region, it is proposed to use chitosan combined with urease-induced calcium carbonate precipitation (EICP) to modify the dump slope of open-pit mines for corrosion and resistance. resistance modification. In this study, the optimal mineralization reaction parameters were determined by testing EICP solutions at different temperatures and dosages. Three groups of slope samples were prepared: control, EICP, and chitosan-targeted-induced EICP, to analyze the erosion condition of the slopes, the erosion volume, and the change rule of the surface strength through the similar model device of the slope corrosion resistance, and to explore the influence of the corrosion resistance characteristics of the slope. corrosion resistance characteristics. The micro-morphology, physical phase composition, and thermal stability of each group of samples were analyzed to investigate the mechanism of chitosan combined with EICP to improve the corrosion resistance of slopes. The results showed that: the optimal reaction parameters for EICPcorrosion resistance of the slope in the drainage field were urea and calcium chloride concentration of 1 mol/L, chitosan doping of 5 g/L, and temperature not higher than 60 ℃; after rainfall erosion, the control group had uneven distribution of surface craters, while there was no obvious change in the modified group, and the final erosion amount of the soil in the EICP and chitosan combined EICP groups was reduced by 85.4% and 91.6%, respectively. and the surface strength was increased by 9.8% and 14.2%, respectively. EICP treatment led to the decrease of soil pH, while the addition of chitosan could stabilize urease activity and ensure urea hydrolysis; chitosan adsorbed urease and Ca2+ to provide nucleation sites for EICP through electrostatic and acid-base interactions, respectively, to promote the production and dispersal of the steady-state mineralization products (calcite) in the EICP and the distribution of the soil. Chitosan hydrogel and mineralization products have the solidifying effects of adhering, bridging, and filling soil particles. At the same time, Ca2+ can drive away the strongly bound water to reduce the thickness of the double layer between particles, thus enhancing the soil structure. Combined with the results of indoor experiments and microscopic tests, the effectiveness of chitosan combined with EICP technology to improve the corrosion resistance of slopes is explained, and the modification mechanism of improving the inter-particle bonding force of soil and reducing the erosive force of the slope surface so as to increase the corrosion resistance of dump slopes is revealed, and the results of the research are expected to be useful for the open-pit mine dump slope erosion control technology. The research results are expected to provide useful reference for the development and engineering application of open-pit mine dump slope erosion prevention technology.